First confirmed ultra-compact dwarf galaxy in the NGC 5044 group - Faifer, Favio Raúl (2017)
Context: Ultra-compact dwarfs (UCDs) are stellar systems displaying colours and metallicities between those of globular clusters (GCs) and early-type dwarf galaxies, as well as sizes of Reff ≲ 100 pc and luminosities in the range −13.5 <MV< −11 mag. Although their origin is still subject of debate, the most popular scenarios suggest that they are massive star clusters or the nuclei of tidally stripped dwarf galaxies. Aims: NGC 5044 is the central massive elliptical galaxy of the NGC 5044 group. Its GC/UCD system is completely unexplored. Methods: In Gemini+GMOS deep images of several fields around NGC 5044 and in spectroscopic multi-object data of one of these fields, we detected an unresolved source with g′ ~ 20.6 mag, compatible with being an UCD. Its radial velocity was obtained with FXCOR and the penalized pixel-fitting (pPXF) code. To study its stellar population content, we measured the Lick/IDS indices and compared them with predictions of single stellar population models, and we used the full spectral fitting technique. Results: The spectroscopic analysis of the UCD revealed a radial velocity that agrees with the velocity of the elliptical galaxy NGC 5044. From the Lick/IDS indices, we have obtained a luminosity-weighted age and metallicity of 11.7+ 1.4-1.2 Gyr and [Z/H] = −0.79 ± 0.04 dex, respectively, as well as [α/ Fe] = 0.30 ± 0.06. From the full spectral fitting technique, we measured a lower age (8.52 Gyr) and a similar total metallicity ([Z/H] = −0.86 dex). Conclusions: Our results indicate that NGC 5044-UCD1 is most likely an extreme GC (MV ~ −12.5 mag) belonging to the GC system of the elliptical galaxy NGC 5044.